Experiential Learning Interventions for In-Service Teachers and Teacher Educators in Science at Secondary Level - Sharma, R. K.; Pareek, R. B. (JOURNAL OF INDIAN EDUCATION, 2024)
In a capacity building programme for the State Resource Groups (SRGs) of 25 teachers or teacher educators from Jammu & Kashmir and Ladakh, experiential learning interventions were given to SRGs to handle experiential learning process in Science at Secondary level by selecting chemical reactions as an exemplar concept. The programme was conducted at the Regional Institute of Education (RIE), National Council of Educational Research and Training (NCERT), Ajmer. During the programme, Kolb’s experiential learning cycle was exercised to give hands-on experience and capacity building of SRGs in the area of chemical reactions in classroom situations by following various stages of experiential learning. As per the interaction and feedback received from the SRGs, the present form of experiential learning intervention has been successful in the capacity building of SRGs to handle the experiential learning process in classroom.